Humour in clinical–educational interactions between graduate student clinicians and people with aphasia. Issue 4 (19th February 2019) - Archer, Brent; Azios, Jamie H.; Moody, Samantha
Abstract: Background: During clinical interactions, clinicians and people with aphasia (PWA) use humour and laughter for a range of purposes, most of which contribute to friendly interactions in which the participants appear to develop a positive regard for one another. Moreover, humour is a vital component of facework, or the processes interactants engage in to protect their own and one another's well‐respected, public personas. Aims: To examine the ways in which speech–language pathology graduate student clinicians enlist humour during one‐on‐one therapy sessions for PWA. Methods & Procedures: Three dyads composed of one graduate student clinician and one person with aphasia acted as participants. We recorded six routine individual aphasia therapy sessions that were each about 60 min in length. All sessions were orthographically transcribed by a trained research assistant. Transcriptions included verbal and non‐speech communication (e.g., facial expressions, gestures, writing). For analysis, we employed an ethnographic microanalysis framework. First, by focusing on laughter produced by the interactants, we identified segments in the data that involved clinician‐led humour. Next, we sought to understand patterns that represented potential functions of humour. We consciously sought out instances that did not appear consistent with our developing understanding of the functions of humour. Such negative cases were used to refine our description of how graduate student clinicians use humour. Other verification procedures included member checking and peer debriefing. Outcomes & Results: The findings illustrate that graduate student clinicians use laughter and humour for a range of interactional purposes when interacting with clients with aphasia. Humour was used as a means of (1) softening exposure to client's errors, (2) equalizing interactional power, (3) mitigating errors made by graduate student clinicians, (4) supporting own narrative production and (5) demonstrating affiliation. Conclusions & Implications: The current study demonstrates that graduate student clinicians we observed, like the clinicians studied in previous investigations of humour in therapeutic encounters, possess the humour and laughter‐related skills that help to foster positive interactions with PWA. Future investigations of the source of these skills should determine if students are adept because of natural abilities or if students can be taught to be better interactants via instruction. Findings emanating from these studies can be used to inform curriculum design, which will in turn help our field better meet the needs of clients.